Development of Antifouling Nanofiltration and Antibiofouling Ultrafiltration Polymeric Membranes Using Facile Protocols - Şeker, Erol; Cihanoğlu, Aydın; Alsoy Altınkaya, Sacide (Izmir Institute of Technology, 2021)
One of the major goals in membrane separation technology is to develop fouling-resistant membranes that can provide a long operating time and low operation costs. This thesis aims to manufacture fouling and biofouling-resistant polymeric nanofiltration (NF) and ultrafiltration (UF) membranes using unique approaches. The first approach was to change coagulation bath composition in the phase inversion technique for manufacturing fouling-resistant polyamide-imide (PAI) based NF and biofouling-resistant polysulfone (PSF)/sulfonated polyethersulfone (PSF-SPES) based UF membranes. To this end, hydrophilic branched polyethyleneimine (PEI) dissolved in the coagulation bath allowed the preparation of a positively charged PAI based NF membrane by forming a covalent bond with the imide group in the PAI. To manufacture antibacterial UF membranes, a strong antibacterial surfactant, cetyltrimethylammonium bromide (CTAB), was dissolved in the coagulation bath and made an electrostatic interaction with SPES at the polymer/bath interface during phase inversion. Both membranes were prepared in a one-step process without using any pore formers in the casting solution. The second approach used in the thesis focused on modification of commercial polyethersulfone (PES) UF membranes with co-deposition of dopamine and CTAB molecules to impart antibiofouling behavior without compromising the pore size and pure water flux of the support. To achieve this task, during modification, an inert physical barrier was created inside the membrane pores by continuously feeding nitrogen gas (N2) from the backside of the support to prevent pore penetration. In the last approach, ultrasound as a green, controllable trigger was used for modifying PSF and PSF-SPES UF membranes with dopamine. The main purpose of using ultrasound was to accelerate the polymerization kinetics of dopamine, hence shortening the modification time.

Membran ayırma teknolojisindeki ana hedeflerden biri, uzun çalışma süresi ve düşük işletme maliyeti sağlayabilen kirlenmeye dayanıklı membranlar geliştirmektir. Bu tezin amacı, özgün yaklaşımlar kullanarak kirlenmeye ve biyolojik kirlenmeye dayanıklı polimerik nanofiltrasyon (NF) ve ultrafiltrasyon (UF) membranları üretmektir. İlk yaklaşımda, kirlenmeye dirençli poliamid-imid (PAI) bazlı NF ve biyolojik kirlenmeye dirençli polisülfon (PSF)/sülfonlanmış polietersülfon (PSF-SPES) bazlı UF membranlarının üretimi için faz değişim yönteminde koagülasyon banyosunun bileşimi değiştirilmiştir. Bu amaçla, koagülasyon banyosunda çözünen hidrofilik dallanmış polietilenimin (PEI), PAI'nın yapısındaki imid grubu ile kovalent bir bağ oluşturarak pozitif yüklü bir NF membranının hazırlanmasına olanak sağlamıştır. Antibakteriyel UF membranları üretmek için, güçlü bir antibakteriyel yüzey aktif madde olan setiltrimetilamonyum bromür (CTAB), koagülasyon banyosunda çözdürülmüş ve faz değişimi sırasında polimer/banyo ara yüzünde SPES ile elektrostatik bir bağ oluşturmuştur. Her iki membran da döküm çözeltisinde herhangi bir gözenek oluşturucu ajan kullanmadan, tek aşamalı bir protokolle hazırlanmıştır. Tezde kullanılan ikinci yaklaşımda, ticari polietersülfon (PES) UF membranının yüzeyi, membranın gözenek boyutu ve saf su akısını değiştirmeksizin dopamin ve CTAB moleküllerinin aynı anda kaplanması ile modifiye edilerek biyolojik kirliliğe karşı dirençli hale getirilmiştir. Modifikasyon sırasında, gözeneklerin içinde kaplamayı engellemek için destek membranının arkasından sürekli olarak azot gazı (N2) beslenerek membranın gözenekleri içinde inert bir fiziksel bariyer oluşturulmuştur. Tezde kullanılan son yaklaşımda, PSF ve PSF-SPES UF membranlarını dopamin ile modifiye etmek için ultrason uygulanmıştır. Ultrason kullanmanın temel amacı, dopaminin polimerizasyon kinetiğini hızlandırmak, dolayısıyla modifikasyon süresini kısaltmaktı.
Kolay Protokoller Kullanılarak Kirlenme Dirençli Nanofiltrasyon ve Biyolojik Kirlilik Önleyici Ultrafiltrasyon Polimerik Membranların Geliştirilmesi
Thesis (Doctoral)--Izmir Institute of Technology, Chemical Engineering, Izmir, 2021
Includes bibliographical references (leaves. 122-141)
Text in English; Abstract: Turkish and English
Keywords: Polymeric membranes; Nanofiltration (NF); Ultrafiltration (UF); Facile protocols